2010
DOI: 10.1021/ja103191u
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Phase Separation and Optical Properties in Conjugated Polymers through Selenophene−Thiophene Copolymerization

Abstract: Selenophene-thiophene block copolymers were synthesized and studied. The properties of these novel block copolymers are distinct from those of statistical copolymers prepared from the same monomers with a similar composition. Specifically, the block copolymers exhibit broad and red-shifted absorbance features and phase-separated domains in the solid state. Scanning transmission electron microscopy and topographic elemental mapping confirmed that the domains are either rich in selenophene or thiophene, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
244
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(255 citation statements)
references
References 28 publications
11
244
0
Order By: Relevance
“…This is apparent when com paring the differences between the normalized absorbance spectra of P3OTbFP3OT with that obtained from a linear combination of the two constituent polymers, P3OT and FP3OT ( Figure S3, Supporting Information). In common to other diblock polymers, such as thiopheneselenophenebased systems, there is a reasonable match between the spectra and the linear combination of the two constituent polymers, [40,41] although similar to the 3:1 diblock [37] polymer it appears that the enhanced backbone planarity and elongated chain of the fluorinated block is partially inhibiting the ordering of the non fluorinated block in this 1:1 copolymer.…”
Section: Thin-film Propertiessupporting
confidence: 54%
“…This is apparent when com paring the differences between the normalized absorbance spectra of P3OTbFP3OT with that obtained from a linear combination of the two constituent polymers, P3OT and FP3OT ( Figure S3, Supporting Information). In common to other diblock polymers, such as thiopheneselenophenebased systems, there is a reasonable match between the spectra and the linear combination of the two constituent polymers, [40,41] although similar to the 3:1 diblock [37] polymer it appears that the enhanced backbone planarity and elongated chain of the fluorinated block is partially inhibiting the ordering of the non fluorinated block in this 1:1 copolymer.…”
Section: Thin-film Propertiessupporting
confidence: 54%
“…[29] Recently our group has shown that selenophene-thiophene block copolymers can be designed to undergo phase-separation into nanostructures in the solidstate, allowing both control of polymer morphology and optical properties without disrupting the conjugated backbone. [30] Although, these studies are early and limited in number, they highlight the potential when conjugated polymers are synthesized from heavier group-16 heterocycles. Tellurophene, the heaviest known group-16 heterocycle, is far less explored for the preparation of conjugated Will polytellurophenes bridge the gap between conjugated polymer and inorganic solid-state semiconductors?…”
Section: Introductionmentioning
confidence: 99%
“…38,39 Although the concept is still preliminary, optimization of the monomer structure as well as the polymerization conditions (for example, catalyst systems) should improve the controllability of quasi-living CTP and provide the ability to synthesize block and gradient polymers. 30,[40][41][42] We are also interested in controlling the axial chirality of the bithiophene dihedral angle by using a chiral ligand; this research is now in progress in our laboratory. …”
Section: Discussionmentioning
confidence: 99%